Covid-19 and its impact on the Malaysian SMEs - Hamir, Mohd. Indra; Rashid, Umi Kartini; Harun, Amran (Penerbit UTHM, 2022)
The spread of the first Coronavirus Disease (COVID-19) in Wuhan, China, shocked the whole world at the end of 2019. The World Health Organization (WHO) declared this epidemic a global pandemic for different countries worldwide on March 11, 2020 (Cucinotta & Vanellli, 2020). Due to this, many countries limited the movement of their people and business activities, and large gatherings, including schools, to effectively transmit the disease (Toda, 2020). On March 18, 2020, the Malaysian government had also announced the Movement Control Order (MCO). People of the country were instructed for a 'social distancing' to enable and resolve the spread of COVID-19.